Monitoring of water quality for sustainable cultivation of golden arowana at Bukit Merah, Malaysia - Sharifhuddin, Norasamullah; Medipally, Srikanth Reddy; Md. Yusoff, Fatimah (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Arowana (Scleropages formosus) is a freshwater bony fish of the family Osteoglossidae, also known as bonytongue or dragonfish. Asian arowana is available in different colours, among these Malaysian golden is the most valuable fish. Malaysian golden arowana is endemic to the Bukit Merah lake Taiping, Malaysia. Because of overfishing and habitat change, arowana is listed as Class 1 Endangered Species by Convention on International Trade in Endangered Species (CITES). Due to high demand as aquarium fish, the arowana aquaculture industry is expanding rapidly in the world, including Malaysia. Water quality and fish health are the two important aspects of productive arowana aquaculture, which are essential for good growth and high production of arowana. However, recent development activities and drought around the lake causing water quality deterioration. Therefore, for sustainable development of arowana industry, water quality management is the crucial factor to maintain the good health status of the fish as well as to counteract the negative impacts on the environment. In this study, we monitored the water quality of arowana farms at Bukit Merah Lake. We selected twelve sampling sites for water quality analysis, of which nine were from different parts of the lake and the rest were from the arowana farm and the supply canal. Based on the present results, water quality in the arowana farms were in the normal condition but according to the standard water quality guidelines some parameters are near to the hazardous level. Therefore, continuous water quality management and preventive measures are needed to maintain the optimum water quality conditions. In this program, we also trained the farm workers to monitor the water source for arowana culture.